Peran-Serta Pemilik Industri Terhadap Perilaku Pemakaian Alat Pelindung Diri Pada Pekerja Pahat Batu di Tamanagung Muntilan - Nurul Asna; Lucky Herawati; Sarjito Eko Windarso (Sanitasi: Jurnal Kesehatan Lingkungan, 2016)
The working environment of stone carving workers in Tamanagung Village of Muntilan has potential hazards that may lead to health problems. Those potential hazards can be preventedthrough proper and routine use of personal protective equipments (PPE). However, in practice,most of the workers are not accustomed to use the PPE. Therefore, the role of the owners toremind and to admonish the workers needs to be realized. This research was aimed to provethat the participation of industry owners can improve knowledge, attitude and practice of PPEamong the carving stone workers. The research design was a quasi experiment with non-randomized pre-test post-test with control group. As the study subjects were workers of nine industries, i.e. 31 workers from four industries were assigned to experiment group and 32 workers from five industries were assigned to control group. The obtained study results show thatthe average value of knowledge, attitude and practice in the experiment group increased, respectively at 9.48; 3.42; and 3.54; meanwhile in the control group, they were at 2.69; 1.44; and2.22; respectively. Non-parametric analysis with Mann Whitney test at 95 % level of significancy found that the improvement differences between the experiment and the control groups forknowledge and attitude of PPE use were significant (p-value < 0.05), and not significant (pvalue = 0,083) for PPE use practice. Based on the results, it can be concluded that participationof industry owners influences the knowledge and attitude of PPE use among their stone carvingworkers.